PENERAPAN HIGIENE DAN SANITASI DI LABORATORIUM TATA BOGA - Yulia Puspitasari; Siti Mariah (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2016)
The purpose of this study is to describe theapplication of hygiene and sanitation in thelaboratory of Boga, including understanding,implementation, and supporting factors and itsinhibitors. The research used descriptivequalitative with object hygiene and sanitationcatering laboratory at State Vocational HighSchool (SMKN) 1 Kalasan Yogyakarta. Methods ofdata collection: observation, interview,documentation. Data validity using triangulationtechnique. Data analysis techniques include datareduction, data presentation, conclusions, andverification. The results show students'understanding of hygiene-sanitation is still low,teachers should always be reminded. Theapplication of hygiene and sanitation in thelaboratory is quite good, it is shown that studentsalways keep clean clothes, nails, hair, cleanenough room, good ventilation, well-groomedsinks, fluid ducts, well-groomed practiceequipment, and neatly arranged. Factorssupporting the implementation of hygiene andsanitation in the laboratory of Boga, namely: theavailability of facilities that are complete enoughto support the smoothness of students practices,cleanliness equipment, and adequate water.Inhibiting factors do not yet have laboratory staff,there are no standard operational procedures(SOP) that regulate hygiene-sanitation in thelaboratory and the sanctions are firm